'Sports - way to success` project as one of sports cluster service models - Litovchenko, V. A.; Zubkov, D. A.; Fendel, T. V. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to rate benefits of a sports promotion project based on a sports clustering model for management efficiency.